NET WORTH UNDER THE DELAWARE AND MICHIGAN CORPORATION LAWS. - Payne, Robert E. (The Accounting Review, 1933)
Abstract The principal effect of a corporation law on financial statements is in the presentation of the net worth accounts. This effect arises from the definitions, sometimes implied, of capital and surplus, and from prescribed methods of establishing, and of increasing or decreasing capital and surplus. It is essential that an accountant, properly to serve and protect the interests of his client, interpret for that client and for the public which relies on the client's financial statements, the effect produced by law on such statements. Only by making a study of the law of the states of incorporation and residence may he determine how the facts may be best displayed. Certain requirements of the Michigan and Delaware Corporation Acts with regard to the capital and surplus accounts of corporations are worthy of special note. By a study of certain sections, and by amplifying and clarifying, the accountant may display the facts in a manner which will more clearly inform clients on important matters, and enable them properly to chart their future course. The discussion in the article deals only with the net worth section of financial statements, such as the display of information showing changes in capital and surplus, and the effect on the balance sheet of a corporation by the purchase of its own capital stock.